Free will and the desire for suicide in mental illness - Zürcher, Tobias (Frontiers in Psychiatry, 2022)
The desire to die brings about the most radical consequences that can occur in a human life. It therefore requires a high degree of justification. Questions have been raised as to whether this justification can be given in the case of a suicide desire in mental illness. Landmark court decisions and the practice of assisted suicide organizations make the justification of a mentally ill person’s suicide desire dependent on the desire not being an expression of the illness. This view is explained in detail and finally rejected as misleading. That argument is based on a conceptual analysis of the self, the nature of reasons for action, and the meaning of necessity with respect to personal autonomy. Against this background, it is shown that it is irrelevant for the assessment of the desire to die whether it has been causally brought about by the mental illness. On the other hand, what matters is whether the person has an internal reason that gives importance to his or her desire. This is to be distinguished from external, normative expectations of a person's "normal" desires. An internal reason that justifies the person's concern must give expression to who the person essentially is and what the person fundamentally cares about. Three objections to this view are formulated, critically evaluated, and rejected. From these considerations it follows that a professional assessment of the desire to die of mentally ill persons must consist primarily in clarifying whether the desire to die fulfills the stated conditions for freedom, irrespective of the mental illness.